2011
DOI: 10.5367/te.2011.0047
|View full text |Cite
|
Sign up to set email alerts
|

Mass Beach Tourism and Economic Growth: Lessons from Tunisia

Abstract: This paper examines the relationship between tourism exports, imports of capital goods and economic growth, with special reference to Tunisia over the period 1975–2007. The dynamic interaction between these variables is examined within a vector error correction model using the Johansen technique of cointegration with structural changes and the multivariate Granger causality test. The authors consider that tourism may affect economic growth through two different channels, the TLG and TKIG mechanisms. Their find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…This is consistent to evidences in Italy (Brida et al, 2010), Tunisia (Cortés-Jiménez et al, 2011) and Greek (Eeckels et al, 2012). Consequently, the findings support the tourism-led economic growth hypothesis and are of particular interest and importance to policy makers, financial analysts and investors dealing with the tourism industry Tourism sector plays an important role in the economic development.…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331supporting
confidence: 77%
“…This is consistent to evidences in Italy (Brida et al, 2010), Tunisia (Cortés-Jiménez et al, 2011) and Greek (Eeckels et al, 2012). Consequently, the findings support the tourism-led economic growth hypothesis and are of particular interest and importance to policy makers, financial analysts and investors dealing with the tourism industry Tourism sector plays an important role in the economic development.…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331supporting
confidence: 77%
“…The studies found that tourism Granger-causes economic growth. However, Cortés-Jiménez et al (2011) found that tourism expansion is the result of economic growth in Tunisia. In the case of Kenya, Kibara et al (2012) found that economic growth is driven by tourism.…”
Section: Insights From the Literaturementioning
confidence: 99%
“…Although Belloumi () found evidence of TLG in Tunisia, Cortés‐Jiménez et al . () rejected it while validating the tourism–capital import–growth (TKIG) hypothesis in the short run. More recently, Bouzahzah and El Menyari () discovered causality from international tourism to economic growth in the short term for Tunisia and Morocco, whereas the reverse causality was found in the long term for both countries.…”
Section: Introductionmentioning
confidence: 97%